Socio Demographic Factors Associated with Osteoporosis among Female in Baghdad - Rashid, Buthaina Ateyah (Diyala Journal of Medicine, 2019)
Background: Osteoporosis is defined as disease in which the density and quality of bone are reduced, leading to weakness of the skeleton and increased risk of fracture, particularly of the spine, wrist, hip, pelvis, and upper arm. Objectives: To find out association of risk factors of osteoporosis and bone mineral density of lumbar spine. Patients and methods: A convenient sample consisted of 150 women were interviewed with special questionnaire in Medical city in Baghdad of not random sample. Results: The results showed that the highest percent of osteoporosis at age group (55-64) years because the aging process leaded to loss of mass and weakening bone. The study presents that cases that have previous family history appeared to be a great risk to develop osteoporosis. Also the result of study showed that most of cases that were not exposing to sun light, low physical activity, always drinking tea and /or coffee, inadequate intake of calcium and vitamin D indicate to have osteopenia or osteoporosis. Conclusion: Female at older age group has greater risk of osteoporosis. Female having past family history of osteoporosis is at high risk of osteoporosis. Inadequate intake of calcium, vitamin D increases the risk of osteoporosis. Drinking (tea, coffee, soft drinks) increase the risk of osteoporosis. Osteoporosis was highly associated with low physical activity.